2015
DOI: 10.1016/j.phrp.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Acinetobacter baumannii in Iran: A Systemic Review of the Published Literature

Abstract: ObjectivesAcinetobacter baumannii is a bacterium responsible for health care-associated infections, and it frequently develops multiple drug resistance (MDR). The prevalence of antibiotic-resistant A. baumannii in Iran has increased, and this may cause significant clinical problems. Therefore, in order to elucidate the development of antibiotic resistance, we performed a systematic review of the literature published on antibiotic-resistant A. baumannii reported in Iran.MethodsThirty-six publications that met t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 42 publications
8
44
0
1
Order By: Relevance
“…According to the report from Moradi et al, the prevalence of MDR isolates between 2008 and 2016 was ranged from 32.7% to 93% (18). The isolation of MDR A. baumannii in the ICU is more common and several outbreaks have been reported from Asian and European countries (8,(18)(19)(20)(21). Antibiotic susceptibility testing in this study showed that 21.8% of patients were infected by resistant strains to all tested antibiotics.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…According to the report from Moradi et al, the prevalence of MDR isolates between 2008 and 2016 was ranged from 32.7% to 93% (18). The isolation of MDR A. baumannii in the ICU is more common and several outbreaks have been reported from Asian and European countries (8,(18)(19)(20)(21). Antibiotic susceptibility testing in this study showed that 21.8% of patients were infected by resistant strains to all tested antibiotics.…”
Section: Discussionmentioning
confidence: 53%
“…In this study, resistance to carbapenems were up to 85% in ICU isolates and the rate of MDR isolates (resistant to beta-lactams, fluoroquinolones, and aminoglycosides) were 54.54%. According to the report from Moradi et al, the prevalence of MDR isolates between 2008 and 2016 was ranged from 32.7% to 93% (18). The isolation of MDR A. baumannii in the ICU is more common and several outbreaks have been reported from Asian and European countries (8,(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Also In another study by karmostaji et al, 54.47% of the isolates were resistant to amikacin, 67.47% to imipenem, and 84.55% of the isolates were resistant to meropenem. Among the 123 isolates, 100 (81.3 %) had an acquired bla (29). The current study tried to evaluate the results of clonal lineage method with the results obtained by PFGE.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review suggested that generally there was an increase in AMDR in throughout the Iran. Researchers suggested that the need for effective surveillance program to prevent AMDR [67].…”
Section: The Islamic Republic Of Iranmentioning
confidence: 99%